2019
DOI: 10.1108/jsocm-02-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

With whom do consumers interact?

Abstract: Purpose The purpose of this study is to investigate the effects of congruent and incongruent anonymous comments posted to an online health news article on personal risk perception. This association is examined through testing the moderating roles of perceived similarity and approval ratings, and the mediating roles of source credibility and content credibility. Design/methodology/approach Hypotheses regarding the impact of comments on personal risk perception were tested experimentally using a news article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Previous studies also discuss how information overload may affect the buying behaviours of people confronting an uncertain situation (Duong et al, 2020). Islam et al (2021) confirm that people experiencing information overload are more likely to make unwise buying decisions and lose self-control.…”
Section: The Relationship Between News Framing and Information Overloadmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies also discuss how information overload may affect the buying behaviours of people confronting an uncertain situation (Duong et al, 2020). Islam et al (2021) confirm that people experiencing information overload are more likely to make unwise buying decisions and lose self-control.…”
Section: The Relationship Between News Framing and Information Overloadmentioning
confidence: 81%
“…Although economic uncertainty has reduced public confidence in policy makers worldwide and the macroeconomic impacts continue to worsen, the repercussions of the Panic buying behavior COVID-19 pandemic for businesses and societies have not yet been revealed (Bapuji et al, 2020;Barua, 2020), thus paving the way for continued information overload. Research argues that personal risk perception may trigger more interactions among people, especially in the face of huge amounts of information about a specific event (Duong et al, 2020;Li et al, 2020), such as the COVID-19 crisis, that they are unable to adequately analyze due to their perceived risk and fear of losing essential commodities of their daily lives (Duong et al, 2020;Phillips-Wren and Adya, 2020). At times of high uncertainty such as the COVID-19 outbreak, the dissemination of mixed messages and tremendous amounts of health and economic information through social media platforms (e.g.…”
Section: The Relationship Between Economic Policy Uncertainty and Inf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, some sources are perceived as more trustworthy than others: People prefer the recommendations and opinions of friends and family. Indeed, online comments of users affect news processing and credibility perception of news content and sources (Duong, Nguyen, & Vu, 2020;Waddell, 2018aWaddell, , 2018b. Referring to the communication channels, the use of a particular communication channel apparently depends on the type of friend (strong versus weak ties) and the communication subject (school subject versus no school subject) (Van Cleemput, 2010).…”
Section: Learning With and Perceived Influenceability By Ytps-videosmentioning
confidence: 99%
“…However, much of the literature has focused on investigating the adverse effects of user-generated comments posted to health promotion videos on attempts to change behaviors (Dubé et al , 2015; Lu and Sun, 2022). More specifically, substantial research has found the detrimental effect of oppositional and negative comments on persuasion outcomes of health promotional messages (Duong et al , 2019; Kim et al , 2021). Subsequently, recommendations to advertisers and social marketers have been centered on engaging in social media listening and monitoring to address public sentiments or limiting users’ ability to provide divisive and opposition comments (Kim et al , 2021; Walther et al , 2010).…”
mentioning
confidence: 99%